Pesquisa de leptospiras e de anticorpos contra leptospiras em animais e humanos de propriedades rurais nos biomas brasileiros pantanal e caatinga - da Silva, Felipe Jorge [UNESP]; Dos Santos, Carlos Eduardo Pereira; Silva, Talita Ribeiro [UNESP]; Silva, Glaucenyra Cecília Pinheiro [UNESP]; Loffler, Sylvia Grune; Brihuega, Bibiana; Alarcon, Miguel Frederico Fernandez [UNESP]; Curci, Vera Cláudia Magalhães; Mathias, Luis Antonio [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2015)
The occurrence of Leptospira and of seroreactivity against Leptospira was investigated in animals and humans from six farms located in two Brazilian biomes that have different geoclimatic conditions: Pantanal - municipalities of Miranda (MS), Itiquira (MT) and Pocone (MT) and Caatinga - municipalities of Sobradinho (BA), Garanhuns (PE) and Sobral (BA). Blood and urine samples of wildlife, domestic animals and humans were collected at each property. The samples were collected from February to April 2012 in Caatinga and from July to September 2012 in Pantanal. The serological reactivity against Leptospira spp. was verified by microscopic agglutination technique (MAT) made with a collection consisting by 24 antigens of Leptospira spp. The leptospires research was carried out by urine samples crop sown in Fletcher resources and Ellinghausen - McCullough - Johnson - Harris (EMJH). Crops with growth of leptospires were referred to the Leptospirosis Laboratory of the Institute of Pathobiology, National Institute of Agricultural Technology, Buenos Aires, Argentina and isolated Leptospira strains were genotyped with the technique of Multiple Locus Variable Number Tandem Repeat Analysis (MLVA). The classification procedure employed the VNTR 4, 7, 9, 10, 19, 23, 31, LB4 and LB5, which discriminate strains of L. interrogans and L. borgpetersenii. In Pantanal, 17 wildlife, 65 domestic animals and two humans were examined. In Caatinga, seven wild animals were examined, along with 100 domestic animals and 26 humans. Of 84 blood samples tested in Pantanal, 47 (55.95%) were positive and, of 133 in Caatinga, 59 (44.36%) were reactant. By Fisher’s exact test, considering a 0.05 significance level, there was no difference between the proportions of serum reagent animals against Leptospira spp. in two biome reviews (p = 0.063). The predominant serovars in SAM reactions were: 1) Pantanal - Bratislava (wildlife, dogs and humans), Grippotyphosa (horses and cattle); 2) Caatinga - Copenhageni (humans and dogs), Patoc (horses and cattle), Panama (sheep and goats), Patoc, Copenhageni and Australis (wildlife). Four strains of Leptospira were isolated: two in Sobradinho, BA, L. interrogans serogroup Pomona in Cavea aperea and L. interrogans in Euphractus sexcinctus; and two in Sobral, CE, L. interrogans in Cerdocyon thous and L. interrogans serogroup Pomona in Euphractus sexcinctus.
Search of leptospires and of antibodies against leptospires in animals and human beings in farms in pantanal and caatinga brazilian biomes
Keywords: Caatinga; Leptospirosis; Pantanal; Serological survey; Urine cultures